Explaining culture scientifically - Brown, Melissa J. (University of Washington Press, 2008)
"What exactly is culture? The authors of this volume suggest that the study of one of anthropology's central questions may be a route to developing a scientific paradigm for the field. The contributors - prominent scholars in anthropology, biology, and economics - approach culture from very different theoretical and methodological perspectives, through studies grounded in fieldwork, surveys, demography, and other empirical data. From humans to chimpanzees, from Taiwan to New Guinea, from cannibalism to marriage patterns, this volume directly addresses the challenges of explaining culture scientifically. The evolutionary paradigm lends itself particularly well to the question of culture; in these essays, different modes of inheritance - genetic, cultural, ecological, and structural - illustrate evolutionary patterns in a variety of settings." "Explaining Culture Scientifically is necessary reading for scholars and students in anthropology and related disciplines."--Jacket.